A scoping review of strategies for financing the implementation of evidence-based practices in behavioral health systems: State of the literature and future directions - Alex R Dopp; Marie-Rachelle Narcisse; Peter Mundey; Jane F Silovsky; Allison B Smith; David Mandell; Beverly W Funderburk; Byron J Powell; Susan Schmidt; Daniel Edwards; Douglas Luke; Peter Mendel (Implementation Research and Practice, 2020)
Background: Increased availability of evidence-based practices (EBPs) is essential to alleviating the negative public health and societal effects of behavioral health problems. A major challenge to implementing and sustaining EBPs broadly is the limited and fragmented nature of available funding. Method: We conducted a scoping review that assessed the current state of evidence on EBP financing strategies for behavioral health based on recent literature (i.e., post-Affordable Care Act). We defined financing strategies as techniques that secure and direct financial resources to support EBP implementation. This article introduces a conceptualization of financing strategies and then presents a compilation of identified strategies, following established reporting guidelines for the implementation strategies. We also describe the reported level of use for each financing strategy in the research literature. Results: Of 23 financing strategies, 13 were reported as being used within behavioral health services, 4 had potential for use, 5 had conceptual use only, and 1 was potentially contraindicated. Examples of strategies reported being used include increased fee-for-service reimbursement, grants, cost sharing, and pay-for-success contracts. No strategies had been evaluated in ways that allowed for strong conclusions about their impact on EBP implementation outcomes. Conclusion: The existing literature on EBP financing strategies in behavioral health raises far more questions than answers. Therefore, we propose a research agenda that will help better understand these financing strategies. We also discuss the implications of our findings for behavioral health professionals, system leaders, and policymakers who want to develop robust, sustainable financing for EBP implementation in behavioral health systems. Plain language abstract: Organizations that treat behavioral health problems (mental health and substance use) often seek to adopt and use evidence-based practices (EBPs). A challenge to adopting EBPs broadly is the limited funding available, often from various sources that are poorly coordinated with one another. To help organizations plan effectively to adopt EBPs, we conducted a review of recent evidence (i.e., since the passage of the 2010 Affordable Care Act) on strategies for financing EBP adoption in behavioral health systems. We present definitions of 23 identified strategies and describe each strategy’s reported (in the research literature) level of use to fund EBP adoption in behavioral health services. Of the 23 financing strategies, 13 strategies had evidence of use, 4 had potential for use, 5 had conceptual use only, and 1 was potentially contraindicated. Examples of strategies with evidence of use include increased fee-for-service reimbursement, grants, cost sharing, and pay-for-success contracts. This comprehensive list of EBP financing strategies may help guide decision-making by behavioral health professionals, system leaders, and policymakers. The article also presents a research agenda for building on the current research literature by (1) advancing methods to evaluate financing strategies’ effects, (2) partnering with stakeholders and decision-makers to examine promising financing strategies, (3) focusing on strategies and service systems with the greatest needs, (4) improving methods to guide the selection of financing strategies, and (5) paying greater attention to sustainable long-term financing of EBPs.